Effect of flow-resistive inspiratory loading on pulmonary and respiratory muscle function in sub-elite swimmers - Shei, R. J.; Lindley, M.; Chatham, K.; Mickleborough, T. D. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of this study was to evaluate the effects of a 12-week swim training and inspiratory muscle training program on respiratory muscle and pulmonary function in competitively trained sub-elite swimmers. METHODS: A double-blind, parallel-group experimental design was employed to compare the effects of swim training alone, swim training with sham-inspiratory muscle training, and swim training with true inspiratory muscle training. Twenty-four competitively trained sub-elite swimmers combined swim training with either flow-resistive inspiratory muscle training set at 80% sustained maximal inspiratory pressure with progressively increased work-rest ratios until task failure for 3 days/week (swim training with inspiratory muscle training, N.=8), or swim training with sham-inspiratory muscle training (N.=8), or acted as controls (swim training only, N.=8). Measures of pulmonary and respiratory muscle function were assessed at the beginning and end of the 12-week study period. RESULTS: At baseline, there were no significant differences (P>0.05) in respiratory muscle and pulmonary function between groups. Following the 12-week training period, the swim training with inspiratory muscle training group demonstrated improvements in maximal inspiratory pressure, sustained maximal inspiratory pressure, maximal inspiratory muscle power output, inspiratory muscle work capacity, inspiratory time of contraction, time to fatigue, maximal voluntary ventilation in 12 seconds, and forced inspiratory volume in 1-second (P0.05). No improvements in pulmonary or respiratory muscle function were observed in the swim training only or swim training with sham-inspiratory muscle training groups (P>0.05). CONCLUSIONS: Inspiratory muscle training in conjunction with swim training improves respiratory muscle function in sub-elite swimmers when compared to swim training only.